Effectivity of Popular Scientific Book “Pteridophyta in Area Loksado” to Improve Students ‘Critical Thinking Skills - Anna Ridhana; Atiek Winarti; Badruzsaufari Badruzsaufari (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Critical thinking is one of the skills that must be developed in the world of education. Students' critical thinking can be improved by optimizing learning, one of which is developing textbooks in the form of popular scientific books. Learning resources can be developed by utilizing the environment around students or locally based. The environment is a very rich source of learning following the demands of the curriculum. In this research, a popular scientific book on the diversity of ferns in the Haratai Loksado waterfall was developed. This study aims to develop popular scientific books based on the local potential to test the effectiveness of popular scientific books in improving students' critical thinking skills. This research is a research development research with formative evaluation using the Tessmer design. The effectiveness was tested at MAN 1 HSS with data on the effectiveness of popular scientific books seen from the average results of evaluation scores and practical results before and after being given popular scientific books. The results of the improvement in critical thinking skills and student learning outcomes were classified as high, namely at the third meeting with the acquisition of 93%. The increase occurred at each meeting as evidenced by the N-gain from the 1st to 3rd meeting with the high category with a value of 0.8.Abstrak Berpikir kritis adalah salah satu keterampilan yang harus dikembangkan oleh pendidikan. Berpikir kritis siswa dapat ditingkatkan dengan mengoptimalkan pembelajaran, salah satunya mengembangkan buku teks berupa buku ilmiah populer. Sumber belajar dapat dikembangkan dengan memanfaatkan lingkungan sekitar atau lokal siswa. Menurut persyaratan kursus, lingkungan merupakan sumber belajar yang sangat kaya. Dalam penelitian ini, dikembangkan buku ilmiah populer tentang keanekaragaman paku di kawasan air Terjun Haratai Loksado. Penelitian ini bertujuan untuk mengembangkan buku ilmiah populer berbasis potensi lokal untuk menguji keefektifan buku ilmiah populer dalam meningkatkan keterampilan berpikir kritis siswa. Kajian ini merupakan kajian penelitian dan pengembangan evaluasi formatif yang dirancang oleh Tessmer. Uji validitas dilakukan pada MAN 1 HSS yang menggunakan data validitas buku ilmiah populer, data diperoleh dari nilai evaluasi sebelum dan sesudah memperoleh buku ilmiah populer serta rata-rata hasil magang. Peningkatan kemampuan berpikir kritis dan hasil belajar siswa tergolong tinggi, yaitu 93% pembelajaran diperoleh pada pertemuan ketiga. N gain (kategori 0.8) dari pertemuan ke-1 sampai ke-3 mengalami peningkatan di setiap pertemuan yang merupakan hasil dari kenaikan tersebut.